Effect of Molecular Weight on Turbulent Drag Reduction with Polyisobutylene - Shanshool, Jabir .; Al-Qamaje, Haider M. T. (Nahrain University College of Engineering Journal, 2008)
Turbulent drag-reduction efficiency of polyisobutylene with three different, very high molecular weights was studied in a build-up closed loop gas oil circulation system. The turbulent mode was produced via a positive displacement gear pump to avoid mechanical degradation of polymer chains during the experimental period. Three molecular weights 2.9*106, 4.1*106 and 5.9*106 g/mol dissolved in reformate were used as additives in order to investigate the effect of molecular weight on drag-reduction rate. The effect of polymer concentration was investigated over a range up to 70 wppm in gas oil flow Reynolds number 8341 to 35747 as well as in 1.25 inch inside pipe diameter. A gradual increase of drag reduction and throughput was achieved by increasing the polymer concentration and gas oil flow rate. Friction factor was calculated from the experimental data. For untreated gas oil pipelining, friction factor values lies near Blasuis asymptotes. While by addition of polymer drag reducer into the flow, the friction factor values were positioned towards Virk maximum drag-reduction asymptotes, noticeably for the highest molecular weight type. Furthermore the investigation showed that the degree of molecular weight is significantly in drag reduction performance. Correlation equations were suggested to predict the effect of flow parameters, concentration, flow rate and finally polymer molecular weight on pressure drop reduction. The results of the correlations showed good agreement between the observed and predicted pressure drop reduction values, with a higher than 97% correlation coefficient.